The impact of organizational culture on the performance of human resources - Mustapha AOUFI; Nacer HAMOUD (Social Sciences Journal, 1970)
This study was an attempt to identify the organizational culture prevailing within theAlgerian organization, the most important characteristics and the exent of thier impact in theperformance of human resources’s level , the researcher has used a descriptive and analyticalapproach which has based on the questionnaire as a key tool for gathering information anddata while the use of sample search method and the application of appropriate statisticaltools to the nature of the search as a mean , standard deviation and correlation coefficiens(Alpha Cronbach , Pearson and Spearman ) and which has carried out of using statisticalprogram(spss).